Simultaneous Nitrification and Denitrification in Aerobic Chemostat Cultures of Thiosphaera pantotropha - Robertson, Lesley A. (1988)
Thiosphaera pantotropha is capable of simultaneous heterotrophic nitrification and aerobic denitrification. Consequently, its nitrification potential could not be judged from nitrite accumulation, but was estimated from complete nitrogen balances. The maximum rate of nitrification obtained during these experiments was 93.9 nmol min(−1) mg of protein(−1). The nitrification rate could be reduced by the provision of nitrate, nitrite, or thiosulfate to the culture medium. Both nitrification and denitrification increased as the dissolved oxygen concentration fell, until a critical level was reached at approximately 25% of air saturation. At this point, the rate of (aerobic) denitrification was equivalent to the anaerobic rate. At this dissolved oxygen concentration, the combined nitrification and denitrification was such that cultures receiving ammonium as their sole source of nitrogen appeared to become oxygen limited and the nitrification rate fell. It appeared that, under carbon-and energy-limited conditions, a high nitrification rate was correlated with a reduced biomass yield. To facilitate experimental design, a working hypothesis for the mechanism behind nitrification and denitrification by T. pantotropha was formulated. This involved the basic assumption that this species has a “bottleneck” in its cytochrome chain to oxygen and that denitrification and nitrification are used to overcome this. The nitrification potential of other heterotrophic nitrifiers has been reconsidered. Several species considered to be “poor” nitrifiers also simultaneously nitrify and denitrify, thus giving a falsely low nitrification potential.